Evangelii Gaudium Education Integration in Catholic Religious Education Lectures to Develop Faith in Church and Community Life - FR Wuriningsih; Soesanto Soesanto; Y L. Sukestiyarno; Titi Prihatin (Universitas Negeri Semarang, 2022)
Catholic Religious Education (PAK) is one of the compulsory subjects taught at non-religious-based Universities. The PAK Lectures with two credits in Higher Education have only reached the accountability of students' faith in church life. This study integrates the Evangelii Gaudium (EG) Education (joy in faith) with the existing concept material. Further, it aims to explore the root cause of the low achievement of dedication to the realization of the community and produce recommendations to achieve trust in the Church and society. This research was carried out with a qualitative approach. The scope of the study is universities in the city of Semarang. The research subjects are key stakeholders, including representatives from the Church or pastors, university students, lecturers, and students. Data retrieval used was triangulation, observations in the Higher Education environment, in-depth interviews with key respondents, and documentation supporting the curriculum. The triangulated data are organized and reduced before concluding. The study results indicate that the Church is satisfied with strengthening faith around the Catholic Church. In fact, in this life, it should be able to penetrate all people in society, including those with different beliefs. Therefore, the practice of faith in the field involving the wider community is deficient.